Quasi-Static and Dynamic Mechanical Properties of a Ti-6Al-4V Titanium Alloy Produced Using Unconventional Manufacturing Methods - Katarzyna J. SARZYŃSKA; Robert PASZKOWSKI (Problemy Mechatroniki)
The purpose of this paper was to determine the mechanical properties of a Ti-6Al-4V titanium alloy produced by traditional CIP (Cold Isostatic Pressing) and by LENS (Laser Engineered Net Shaping), an additive manufacturing process. A reference material, being a commercial Ti-6Al-4V alloy, was also tested. The strength test specimens were produced from a high-quality, Grade 5 titanium powder. Each specimen had its density, porosity, and hardness determined. Compression curves were plotted for the tested materials from the strength test results with static and dynamic loads. These tests were performed on an UTS (Universal Testing Machine) and an SHPB (Split Hopkinson Pressure Bar) stand. The test results obtained led to the conclusion that the titanium alloy produced by CIP had lower strength performance parameters than its commercially-sourced counterpart. The LENS-produced specimens outperformed the commercially-sourced alloy both in static and dynamic load conditions.